Scientometric analysis of glioblastoma and blood-brain barrier research (1995−2024): evolving trends and therapeutic challenges - Pan, Xuan-Hao; Wang, Nan; He, Yi-Chun; Su, Jing; Gao, Yu-Fei (Frontiers in Oncology, 2025)
BackgroundGlioblastoma (GBM) is one of the most aggressive neurogenic tumors. Despite advances in treatment, the presence of the blood-brain barrier (BBB) continues to pose significant challenges to effective therapeutic delivery. However, to date, no comprehensive bibliometric analysis has systematically evaluated the relationship between GBM and the BBB over the past three decades.ObjectiveThis study provides an overview of research progress on GBM and the BBB, with emphasis on structural and functional changes of the BBB. It also identifies current research hotspots, predicts emerging trends, and offers insights for future investigations. Method: Literature from the past 30 years was retrieved from the Web of Science Core Collection and PubMed. Bibliometric analysis was performed using the R programming language, and data visualization was conducted with VOSviewer, CiteSpace, and Tableau.ResultSince 2015, publication output and academic influence in this field have increased exponentially. The United States leads in both publication volume and citation count, and engages in extensive international collaborations. Cancer Research, the leading journal in this field, ranks first with 6,775 citations over the past 30 years. Keyword analysis reveals that the field has primarily focused on tumor-associated angiogenesis, the role of vascular endothelial growth factor (VEGF) in BBB disruption, optimization of drug delivery strategies, the influence of the tumor microenvironment (TME) on tumor progression, and advances in precision medicine. Co-citation analysis, citation burst detection, and Latent Dirichlet Allocation (LDA) topic modeling have identified seminal publications and key developmental trajectories. Notably, a comprehensive analysis of clinical trial literature revealed a gradual shift in research focus from traditional morphological and single-agent efficacy studies to more integrated approaches, including BBB permeability regulation, targeted drug delivery, and multimodal functional imaging.ConclusionThis study offers a comprehensive overview of GBM−BBB research trends over the past 30 years. It advances the understanding of their interplay and provides theoretical guidance for overcoming the BBB and improving GBM outcomes.